Gun violence and gun control: critical engagements - Bailey, Annette; Harrison, Thomas; Bromwich, Rebecca (Demeter, 2022)
"This interdisciplinary anthology explores a wide range of intersecting issues contributing to and arising from gun violence. Millions of people are hurt and killed by gun violence globally, and the traumatic realities of these events are navigated by individuals and communities widely. In this context, gun violence fundamentally threatens social functioning in significant ways, and profoundly test the resilience of families. The resulting transformations carry social, political, legal and economic implications for mothering, family dynamics, and community engagement. This collaborative volume brings together diverse perspectives intended to deconstruct perceptions, realities, risks and impacts of gun violence, as seen by researchers, educators, community advocates, public health/health care experts, criminologists, social workers, field-based practitioners, and victims/survivors of gun violence. The distinct and broad range of contributions in this volume critically unpacks representations, stress and trauma, resilience, advocacy/activism, policymaking, family functioning, social justice and equity, governmentality and the criminal justice system, public health/health care, and community programs/interventions. Ultimately, the work is a unique contribution to the literature in which there is a lack of wide academic consideration of gun violence and a demonstrably unsatisfactory political response stretching back decades."--